PENGGUNAAN METODE DALAM PEMBELAJARAN AL-QUR’AN - Husyin Saputra; Rubi Awalia (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2023)
The ability to read the Koran is a basic skill that must be possessed by every Muslim. Remembering the Koran as the holy book of Muslims as well as a life guide towards the path of truth. This ability includes accuracy in reciting al- Qur'an readings according to the correct tajwid and makhraj. In learning the Qur'an using: (1) The Al-Qur'an learning method used is the Dirosa method. The Dirosa method is a pattern of fostering the Qur'an and Islamic foundations which is managed in a systematic, tiered and continuous manner, (2) The implementation of learning the Qur'an starts with the teacher carrying out the learning process using the classical and drill system. The dirosa learning program consists of; (a) classical program for beginners. This program is intended for participants who cannot read the Koran (from scratch), or who are still stuttering, not correctly pronouncing the letters (makhroj) and in short lengths and not yet tartil the Koran. (b) advanced program. This program is intended for participants who are fluent in reading the Qur'an but there are still reading errors (not yet perfect according to the rules of tajwid science). Dirosa's learning steps are: technique 1 (T1) the teacher reads the material, participants point to writing, technique 2 (T2) guides. The teacher reads the material then the participants imitate it, technique 3 (T3) read together, technique 4 (T4) imitate. Participants read one by one and imitated other participants, technique 5 (T5) reading in pairs, and reading independently.